Wolbachia infection prevalence as common insects’ endosymbiont in the rural area of Yogyakarta, Indonesia - Dian Aruni Kumalawati; Endah Supriyati; Mifta Pratiwi Rachman; Rizky Oktriani; Irianti Kurniasari; Damiana Sapta Candrasari; Lisna Hidayati; Anastasia Evi Handayaningsih; Viera Cristalia Probowati; Budi Arianto; Dwi Satria Wardana; Nida Budiwati Pramuko; Adi Utarini; Warsito Tantowijoyo; Eggi Arguni (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kumalawati DA, Supriyati E, Rachman MP. Oktriani R, Kurniasari I, Candrasari DS, Hidayati L, Handayaningsih AE, Probowati VC, Arianto B, Wardana DS, Pramuko NB, Utari A, Tantowijoyo W, Arguni E. 2020. Wolbachia infection prevalence as common insects’ endosymbiont in the rural area of Yogyakarta, Indonesia. Biodiversitas 21: 5608-5614. Control for mosquito-borne diseases such as dengue and chikungunya using vectors is urgently required. The World Mosquito Program, a multinational collaborative research program, is currently studying for the ability of Wolbachia-infected Aedes aegypti to control dengue. Community concerns on Wolbachia's natural existence in their surrounding living area. This study presents the field study of Wolbachia pipientis in insects commonly found in rural daily life. W. pipientis is an endosymbiotic bacterium commonly found in arthropods. Insects were collected from five villages in Sleman and Bantul District, Yogyakarta Province, Indonesia, from July to December 2012 and screened for Wolbachia infection using PCR. One hundred insects, including butterflies, moths, mosquitoes, flies, were collected. The results indicated that 44.9% of identified insect species were positive for Wolbachia pipientis, which support the existing data from other regions on the spread of Wolbachia infection in insects.